2017
DOI: 10.1002/prep.201700208
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Some Amines on Ignition Delay Time of Dimethyl Amino Ethyl Azide (DMAZ) and White Fuming Nitric Acid (WFNA)

Abstract: Dimethyl amino ethyl azide (DMAZ), as a non‐carcinogen liquid fuel, is a good fuel in space programs. However, it suffers from high ignition delay (ID) time with liquid oxidizer white fuming nitric acid (WFNA). DMAZ were blended with amines in order to reduce the ID time of bipropellant DMAZ‐WFNA. A drop‐on‐pool impingement set‐up, coupled with a high‐speed camera, was applied to investigate the ID time at ambient pressure and temperature. It was found that using of amines had dissimilar effects on the ID time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The ignition delay of DMAZ was approximately 26 ms. When 33.3% DMAZ and 66.7% TMEDA were added into the fuel mixture, the ignition delay could be adjusted to 9 ms. 19 Pakdehi 20 carried out a dripping experiment under environmental pressure and temperature with the aid of a high-speed camera to add several amines as compounding agents to DMAZ and measured the ignition delay time between them and white fuming NA (WFNA). The results showed that adding pyrrole, tert-butylamine, and octylamine to DMAZ significantly shortened the ignition delay of DMAZ and WFNA.…”
Section: Introductionmentioning
confidence: 99%
“…The ignition delay of DMAZ was approximately 26 ms. When 33.3% DMAZ and 66.7% TMEDA were added into the fuel mixture, the ignition delay could be adjusted to 9 ms. 19 Pakdehi 20 carried out a dripping experiment under environmental pressure and temperature with the aid of a high-speed camera to add several amines as compounding agents to DMAZ and measured the ignition delay time between them and white fuming NA (WFNA). The results showed that adding pyrrole, tert-butylamine, and octylamine to DMAZ significantly shortened the ignition delay of DMAZ and WFNA.…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl aminoethyl azide (DMAZ) is a suitable candidate for replacement of hydrazine fuels in space programs. It is non‐carcinogen and has good physicochemical and performance properties 1–3. In the production process of DMAZ, the final product always contains 2–5 wt % of water 4.…”
Section: Introductionmentioning
confidence: 99%